Sense of Sovereignty. How national sentiments have influenced Iceland's European policy - Eiríkur Bergmann Einarsson (2009)
Fræðigrein This paper asks why Iceland had until July 2009 chosen to participate in the European project through the EEA and Schengen agreements but not with full membership in the EU. It analyses if and how ideas on the Icelandic nation and its sovereignty affects the stance Icelandic politicians have taken towards the European project. Icelanders’ struggle for independence in the 19th century created a special kind of nationalism which gives prominence to the sovereignty of the nation as a whole. Economically, however, Iceland feels the same need as other European states to participate in European co-operation, which can explain its membership in the EEA. The agreement brings Iceland into the European single market, but at a cost: Iceland has de-facto agreed to adopt the EU’s legislation within the boundaries of the agreement, and thus a transfer of decision making and domestic governmental power to the EU. This dilemma, between economic interests on the one hand and ideas on the sovereignty of the Icelandic nation on the other, has created a kind of a rift between the emphasis on the free and sovereign nation and the reality Iceland is faced with in the co-operation. The inheritance of the independent struggle still directs the discourse Icelandic politicians use in the debate on Europe. A strong emphasis on sovereignty has become the foundation on which Icelandic politics rests. Participation in EU’s supra-national institutions falls, in a way, outside the framework of Icelandic political discourse, which highlights Iceland’s sovereignty and stresses an everlasting independence struggle.